Efforts to Improve Teacher Performance in The Learning Process at SMPN 1 Wawotobi (Edukasi, 2022)
This study expects to decide endeavors to further develop educator execution in the educational experience at SMPN 1 Wawotobi and to break down the elements that impact educator execution in the growing experience at SMPN 1 Wawotobi. Information assortment was helped out through meetings, perception and report survey. In order to draw more objective conclusions from a study, the data that has been gathered are then classified, analyzed, and interpreted in detail. Through teacher performance in the learning process at SMPN 1 Wawotobi, the results demonstrated that efforts to improve teacher performance in the learning process had been successful: a) Teaching quality and quantity: in terms of teaching quality, the teacher had carried out the learning process well and in accordance with expectations, and in terms of teaching quantity, the number of teachers was sufficient and had carried out their responsibilities in the classroom; b) Teaching is completed promptly in accordance with school policies and procedures; c) routine learning tasks have been carried out in accordance with the goals of the school organization through cooperation between fellow teachers and leaders in the implementation of education in the school environment.